2022
DOI: 10.1001/jamanetworkopen.2022.10880
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Outcomes and Factors Associated With Mortality Among Patients With SARS-CoV-2 Infection and Cancer Compared With Those Without Cancer

Abstract: This systematic review and meta-analysis analyzed the association of age, sex, and cancer types and therapies with survival rates among patients with both cancer and COVID-19 diagnosis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 116 publications
(1,775 reference statements)
4
60
1
3
Order By: Relevance
“…As a result, since the beginning of 2022 there has been a renewed interest toward CCP use, particularly for immunocompromised patients, who are not able to mount a sufficiently protective antibody response against the virus and have contraindications or side effects from small molecule antivirals (11, 12). These patients are at higher risk for morbidity and mortality from COVID-19 (13). A few controlled studies and a number of case reports and case series have shown a clinical benefit from CCP use for COVID-19 patients with hematological or solid cancer or other underlying causes of immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, since the beginning of 2022 there has been a renewed interest toward CCP use, particularly for immunocompromised patients, who are not able to mount a sufficiently protective antibody response against the virus and have contraindications or side effects from small molecule antivirals (11, 12). These patients are at higher risk for morbidity and mortality from COVID-19 (13). A few controlled studies and a number of case reports and case series have shown a clinical benefit from CCP use for COVID-19 patients with hematological or solid cancer or other underlying causes of immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical outcomes were much worse, particularly in patients with cancer affected by COVID-19. In a meta-analysis, which included a total of 81 studies (19 for mortality) and 61532 participants, conducted by Khoury et al [17], a signi cant increase in mortality was reported in patients with cancer affected by COVID-19 (RR = 2.12, 95% CI: 1.71-2.62, p < 0.001, I 2 = 84.4%). They also reported an increased mortality in patients with hematological (RR = 1.42, 95% CI:…”
Section: Discussionmentioning
confidence: 99%
“…It is now well-established that coronavirus disease 2019 (COVID-19) in patients with cancer carries a higher morbidity and mortality, especially in patients with hematologic malignancies [1][2][3][4][5]. While overall case fatality has decreased over time, mostly related to the impact of broad vaccinations and improved supportive/antimicrobial management, a higher case fatality rate was noted amongst cancer patients even during the Omicron (B.1.1.529) wave [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%